2018
DOI: 10.3390/cells7050038
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Derived iPSCs and iNs—Shedding New Light on the Cellular Etiology of Neurodegenerative Diseases

Abstract: Induced pluripotent stem cells (iPSCs) and induced neuronal (iN) cells are very much touted in terms of their potential promises in therapeutics. However, from a more fundamental perspective, iPSCs and iNs are invaluable tools for the postnatal generation of specific diseased cell types from patients, which may offer insights into disease etiology that are otherwise unobtainable with available animal or human proxies. There are two good recent examples of such important insights with diseased neurons derived v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Analyses of forebrain organoids from MOPD I patients showed reduced proliferation, premature neuronal differentiation, increased horizontal cell divisions in VZ-like areas, and reduced radial glial migration. Patient-derived iPSCs offer an opportunity to uncover molecular mechanisms behind microcephaly, as they have been successfully used to model human neurological disorders in vitro since they possess the same genetic make-up of the individual that they were derived from (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). In addition, modeling these neurodevelopmental disorders in mice is not ideal since the mouse brain is lissencephalic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of forebrain organoids from MOPD I patients showed reduced proliferation, premature neuronal differentiation, increased horizontal cell divisions in VZ-like areas, and reduced radial glial migration. Patient-derived iPSCs offer an opportunity to uncover molecular mechanisms behind microcephaly, as they have been successfully used to model human neurological disorders in vitro since they possess the same genetic make-up of the individual that they were derived from (61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72)(73). In addition, modeling these neurodevelopmental disorders in mice is not ideal since the mouse brain is lissencephalic in nature.…”
Section: Discussionmentioning
confidence: 99%
“…That may be too simple, although it is a strategy worth evaluating. However, this should not be done with pre-clinical animal models due to known differences in inflammatory responses compared to humans, but in human iPSC ex vivo models that incorporate elements of the blood-spinal cord barrier (BSCB)BBB/NVU along with neurons (156, 157).…”
Section: Connecting Dots To Neurodegeneration: Neuroinflammation Coamentioning
confidence: 99%
“…The cells directly converted to neuronal cells are called "induced-neuronal (iN) cells" and were first developed from mouse fibroblasts transfected with the three transcriptional factors Brn2, Ascl1, and Myt1l (BAM factors) [23]. Human iN cells have been utilized in neuropsychiatric research, [24,25] and several advantages have been reported that iN cells retain some of the aging-related physiological conditions that are lost in iPS cells [26,27]. Using human-derived BAM factors, we succeeded in inducing iN cells from adult human fibroblasts in 2 weeks [28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%